2011
DOI: 10.1166/jnn.2011.4446
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Graphene-Gold Nanocomposites via Sonochemical Reduction

Abstract: A Reduced reduced graphene oxide (RGO)-gold (Au) nanoparticle (NP) nanocomposite was synthesized by simultaneously reducing the Au ions and depositing Au NPs on onto the surface surface of the RGOsRGO simultaneously. To facilitate the reduction of Au ions and the generation of oxygen functionalities for anchoring the Au NPs on the RGOsRGO, ultrasound irradiation was applied to the mixture of reactants. The functional groups were investigated with FT-IR spectra. From the Raman and XPS spectra, the oxygen groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For example, Park et al reported the synthesis of rGO–AuNPs nanocomposites by simultaneous reduction and deposition of AuNPs onto the surface of rGO by ultrasonic irradiation. Here, the attachment of AuNPs onto the rGO surface is mediated via the electrostatic attraction of Au ions to oxygen functionalities on the rGO surface [104]. On the other hand, Vinodgopal et al [105] reported simultaneous and sequential reduction of GO and HAuCl 4 in 2% polyethylene glycol aqueous solution to fabricate rGO–Au nanocomposites by maintaining an ultrasonic frequency of 211 kHz.…”
Section: Fabrication Of Graphene–gold Nanocompositementioning
confidence: 99%
“…For example, Park et al reported the synthesis of rGO–AuNPs nanocomposites by simultaneous reduction and deposition of AuNPs onto the surface of rGO by ultrasonic irradiation. Here, the attachment of AuNPs onto the rGO surface is mediated via the electrostatic attraction of Au ions to oxygen functionalities on the rGO surface [104]. On the other hand, Vinodgopal et al [105] reported simultaneous and sequential reduction of GO and HAuCl 4 in 2% polyethylene glycol aqueous solution to fabricate rGO–Au nanocomposites by maintaining an ultrasonic frequency of 211 kHz.…”
Section: Fabrication Of Graphene–gold Nanocompositementioning
confidence: 99%
“…26 Subsequently, oxygencontaining groups served as the links for AuNPs to control the growth of Au nanocrystals. 27 Thus, the oxygen-containing groups on GO controlled the diffusion of the AuCl 4 À ions, the subsequent generation of Au nuclei at the initial beginning stage and the growth direction of the Au nanocrystals in the electrochemical synthesis process. The mechanism of GO as the morphology-controlling agent for the synthesis of DAuNs was also illustrated in Scheme 1.…”
Section: Mechanism For the Controlled Synthesis Of Daunsmentioning
confidence: 99%
“…Our group applied the ultrasound irradiation method for the fabrication of metal-doped silica nanocomposites [8,11,23,24]. The acoustic cavitation phenomenon facilitates interparticle collision between metal and support material, inducing the binding between metal and support [25,26].…”
Section: Ultrasound-assisted Catalyst Synthesismentioning
confidence: 99%